ANALISIS FAKTOR INTERNAL DALAM KEBIASAAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SDK NEKO LENGOR KECAMATAN ELAR SELATAN KABUPATEN MANGGARAI TIMUR - Adam Bol Nefu Benu; Fulgentino Kelvin Sanatalen; Marselus Robot (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the study habits of SDK Neko Lengor students and internal factors in study habits. This research uses a qualitative approach with a case study type of research. Data collection techniques use observation, interviews and documentation. The sample in this study was 7 class V students at SDK Neko Lengor, the homeroom teacher for class V, and the students' parents. The location used in this research was SDK Neko Lengor, South Elar District, East Manggarai Regency. The research results show that SDK Neko Lengor students have different study habits, such as studying before exams, studying while doing assignments, and studying because they want to get good grades. The internal factors that influence students' learning habits consist of several factors, namely students' interest in Indonesian language subjects, student motivation, attention and student health. From the results of this research, it can be concluded that there are several internal factors that can influence the learning methods and habits of class V students at SDK Neko Lengor.